Impact of rounded electrode corners on breakdown characteristics of AlGaN/GaN high-electron mobility transistors. (18th April 2018) - Yamazaki, Taisei; Asubar, Joel T.; Tokuda, Hirokuni; Kuzuhara, Masaaki
Abstract: We investigated the impact of rounded electrode corners on the breakdown characteristics of AlGaN/GaN high-electron mobility transistors. For standard reference devices, catastrophic breakdown occurred predominantly near the sharp electrode corners. By introducing a rounded-electrode architecture, premature breakdown at the corners was mitigated. Moreover, the rate of breakdown voltage ( V BR ) degradation with an increasing gate width ( W G ) was significantly lower for devices with rounded corners. When W G was increased from 100 µm to 10 mm, the V BR of the reference device dropped drastically, from 1, 200 to 300 V, whereas that of the rounded-electrode device only decreased to a respectable value of 730 V.